Achieving Effective Math Learning with Animated Video-Based Media: A Study on 11th-Grade Students - Rasmini, Rida; Berngacha, Suhairee (The Indonesian Institute of Science and Technology Research, 2023)
This study aimed to develop animated video-based learning materials tailored to the learning trajectory of 11th-grade students in the second semester. The Renderforest application facilitated the creation of these instructional videos. The research employed a developmental approach utilizing the ASSURE model. The research participants comprised 11th-grade students. Data collection methods included questionnaires and semi-structured interviews conducted indirectly. The study's outcomes were primarily based on student feedback and validation by media experts. The developed instructional media demonstrated feasibility and practicality, as confirmed through validity and practicality assessments. Media expert validation yielded an average score of 3.7, indicating that the instructional video met the criteria for being excellent and suitable for educational use. Additionally, the students' responses yielded an average score of 3.8, meeting the requirements for being excellent and convenient for instructional purposes. These materials align with the student's learning trajectory and can enhance the overall learning experience in the educational context.